Methylation patterns of testis-specific genes. - Ariel, M (1991)
The methylation patterns of genes expressed in the mouse male germ line have been examined. Int-1, Hox-2.1, and Prm-1, all of which contain 5' CpG islands, were found to be completely unmethylated at many sites in these domains, both in somatic tissues and in sperm DNA. Many other testis-specific genes have a similar structure and are probably also constitutively unmethylated. Pgk-2, a non-CpG-island gene, is similar to somatic tissue-specific genes in that it is highly methylated in nonexpressing cell types but undermethylated in pachytene spermatocytes and round spermatids, where it is actively transcribed. At later stages of spermatogenesis, however, the gene becomes remethylated and thus acquires the full modification pattern in sperm DNA. In all these cases, the sperm DNA that emerges from the testis does not contain any germ-line-specific unmethylated sites and thus carries the methylation pattern typical of that in somatic tissues.